Ensino da matemática no contexto do Programa Ensino Médio Inovador - PROEMI : uma análise sobre práticas pedagógicas - Silva, Benedito Eduardo da (2018)
The present research is about an investigation about the teaching of mathematics in high school and pedagogical practices according to the restructuring of High School, through the acceptance of the implementation of the Innovative High School Program at a State School in the interior of the State of Mato Grosso. This school, serves only students in the final stages of basic education, high school and the different offers of education. The Regular High School Night, the High School Integrated to the Professional Education - EMIEP, with the Technical Course in Computer Science and the High School Innovation, that reaches the majority of the students in the morning and evening shifts, with a more extensive workload and complementary differentiated pedagogical actions that are implanted in the school curriculum as projects and within the school's Political-Pedagogical Project. It is worth emphasizing that this research has the focus directed to the Mathematics discipline and the professors that teach this discipline only in the High School Innovation. The actions related to pedagogical practices that are used in the teaching of mathematics in the final series of basic education are great challenges for the educator as well as for the student. Accustomed to the traditional teaching method, they tend to use creativity and knowledge to present a new way of learning mathematical concepts and their applicability in everyday school life and even outside it. It is a qualitative perspective research, with the main objective of analyzing the propositions and pedagogical practices in the teaching of Mathematics in a public school located in Poconé, in the interior of Mato Grosso, which joined the Innovative High School Program - PROEMI from the year of 2011. The methodology was developed with the collection of data obtained through daily school observation and semi-structured interview that was later transcribed, applied to teachers who teach mathematics classes to the classes of Innovative High School and follow up on the execution of actions of pedagogical practices. This research leads us to a reflection about teacher training and the reality of programs created without previous training for its execution. The difficulty of students in the study of mathematics. The vision of the teachers to continue a methodology that, according to them, worked. Development of pedagogical practices that stimulate students. Actions that go beyond the limits of the classroom.